Brazil’s benign breast disease care profile and geospatial analysis - Dayan Sansone; Daniela Farah; Afonso Celso Pinto Nazario; Marcelo Cunio Machado Fonseca (Einstein (São Paulo))
ABSTRACT Objective To quantitatively and geospatially analyze coverage and displacement for the diagnosis and treatment of benign breast diseases in the Brazilian Unified Health System between 2008 and 2019. Methods Datasets from the Brazilian Ministry of Health were used to survey medical care for benign breast diseases in Brazil from 2008 to 2019. These data allowed for the determination of benign breast disease treatments, diagnoses, and patient displacement in each region of the country. Results Most outpatient consultations were for diagnostic procedures. Approximately 4 million diagnostic procedures and 360,000 hospitalizations for treatment, of which 97% were surgeries, were conducted in this 12-year period. During this period, medical care for benign breast diseases cost more than USD 65 million. The treatment coverage and displacement rates of the female population differed by country region, with the North and Midwest showing patterns different from those of the other three major regions. Conclusion Addressing disparities in healthcare service access, regardless of their source, by increasing the service capacity of existing facilities and ensuring correct resource allocation by the healthcare system is crucial.